2010
DOI: 10.3109/01902148.2010.482176
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor (EGFR) mutation and p-EGFR expression in resected non-small cell lung cancer

Abstract: Lung cancer, specifically non-small cell lung cancer (NSCLC), is a leading cause of mortality worldwide. In China, a dramatic increase in the incidence of NSCLC is expected in the next 20 years (Molina et al. Mayo Clin Proc. 2008;83:584–594). Mutated epidermal growth factor receptor (EGFR) status is a known predictor of response to tyrosine kinase inhibitors (TKIs), and immunohistochemistry may be a less costly way of predicting presence of mutation. In this study, mutation analysis of EGFR in 218 cases of NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Mutations at tyrosine 1045 codon of EGFR have been shown to interfere with its phosphorylation and ability to interact with c-Cbl (Kirisits et al, 2007). This was also confirmed in a recent case control study, where in phosphorylation at tyrosine 1045 residue was observed only in 52% of 218 cases of non-small cell lung cancers (NSCLCs) that were analyzed (McMillen et al, 2010). The lack of phosphorylation in rest of the tumor samples may have been due to a mutation at the tyrosine 1045 region, but was not analyzed.…”
Section: Introductionsupporting
confidence: 52%
“…Mutations at tyrosine 1045 codon of EGFR have been shown to interfere with its phosphorylation and ability to interact with c-Cbl (Kirisits et al, 2007). This was also confirmed in a recent case control study, where in phosphorylation at tyrosine 1045 residue was observed only in 52% of 218 cases of non-small cell lung cancers (NSCLCs) that were analyzed (McMillen et al, 2010). The lack of phosphorylation in rest of the tumor samples may have been due to a mutation at the tyrosine 1045 region, but was not analyzed.…”
Section: Introductionsupporting
confidence: 52%
“…Although identification of patients who respond to EGFR inhibitors based on mutational analysis and alternate pathway activation has been a poster child for pharmacogenomics, 3141 recent reports indicate that mutational status may be accurately predicted by EGFR phosphorylation patterns, especially Y1068 and Y1045 15,49 and Y1173, 42 and thus, protein phosphorylation profiling of EGFR may provide a new companion diagnostic assay method for selection and stratification for therapy. 50 Development of quantitative approaches to measure EGFR phosphorylation, such as by RPMA, can be used to identify optimal cutpoints for molecular correlates, and a more comprehensive quantitative survey of the many EGFR phosphorylation sites (we measured seven different sites) along with downstream signaling analysis through AKT and ERK could yield better response prediction to EGFR inhibitors. The fact that AKT and mTOR pathway activation were found in patient subgroups in which both modules were activated simultaneously or alone indicates the potential to stratify patients for combination therapeutics that target PI3K-AKT and downstream mTOR together, or PI3K and mTOR inhibitors alone.…”
Section: Discussionmentioning
confidence: 99%
“…Erlotinib also failed to demonstrate significant activity in other EGFR-driven cancers, such as glioblastoma [16] and esophageal cancer [17]. Of note, in non-small cell lung cancer, presence of a mutated EGFR appeared to be linked to expression of phosphorylated EGFR [18]. As phosphorylated EGFR is expressed in PC, we hypothesized that the same mutations could be present in PC and be responsible for EGFR activation.…”
Section: Egfr Mutational Status In Penile Cancermentioning
confidence: 96%